Creating a Better Patient Safety Culture in Taiwan: The Viewpoints of Physicians and Registered Nurses - Chih-Hsuan Huang; Hsin-Hung Wu; Yii-Ching Lee; Li Li; Cheng-Feng Wu (Baqiyatallah University of Medical Sciences, 2017)
Background: Patient safety culture in healthcare organizations has become an important issue globally for improving medical services. In 2016, Taiwan's National Health Insurance (NHI) system covered 99.6% of Taiwan's population. With the enhancement of medical quality, patients expect medical service providers to care more about safety and medical service. Understanding physicians and registered nurses' attitudes toward patient safety is a critical issue for healthcare organizations wanting to improve the quality of the medical care they provide. Objective: The purpose of this study was to discern physicians and registered nurses' attitudes toward patient safety using Sexton and colleagues' Safety Attitudes Questionnaire (SAQ) in order to develop strategies for improving the quality of medical services. Methods: Pearson correlation analyses were conducted to demonstrate the relationships among six patient safety culture dimensions. Physicians and registered nurses were asked to complete the questionnaire in a case hospital in Taiwan in 2016. Results: The results of Pearson correlation analyses demonstrated a strong and positive relationship between perceptions of management and working conditions. Additionally, teamwork climate was highly correlated to safety climate. The results also illustrated that teamwork climate and job satisfaction were significantly related. Conclusion: The assessment of patient safety culture can provide a basis for hospital managers to monitor the quality of the medical care provided at their organizations. Hospital managers should put more efforts into the essentially important elements of patient safety culture, such as teamwork climate, safety climate, perceptions of management, and working conditions, so as to continuously improve the quality of medical care.